Narratives of Self-harm: the experience of young women through the qualitative analysis of blogs - Anna Gargiulo; Giorgia Margherita (Mediterranean Journal of Clinical Psychology, 2019)
In the last few years, an increasing number of studies have investigated the Self-harming behaviours, particularly widespread among young women, and the development of websites relating to Self-harm, in which the users are most often females. From a psychodynamic perspective, this article aims at identifying the most prevalent topics shared in blogs written by young people who Self-harm, in order to understand their experiences of suffering. We performed a thematic analysis of 70 Italian blogs relating to Self-harming behaviours. From our analysis all the blogs were declined in the feminine. Four thematic clusters were found: troubled relationships with the Other; the hidden Self; loneliness, hate and guilt: the melancholic emotions; the Self-harming act. Some specific functions of Self-harm blogs emerged: they can be a mean for self-disclosure and for emotion regulation. They are also spaces where young women meet to share their pain and offer and find support. Clinical implications for blogs as a place for illness narratives will be discussed.